OPTIMIZATION OF THE OPERATIONAL DATABASE FOR DISINFECTION SERVICES AND IMPLEMENTATION OF PARALLEL PROCESSING MECHANISMS IN POSTGRESQL - Mayil Azmammadov (Research Reviews, 2026)
The article investigates the design and performance optimization of an operational database for the disinfection service sector. In the modern service environment, real-time data processing, concurrent access by multiple users, and rapid generation of analytical reports require a reliable and high-performance database architecture. Within the scope of the study, the integration of OLTP and DWH models on the PostgreSQL platform, the selection of efficient indexing strategies, table partitioning, and the implementation of parallel processing mechanisms were analyzed. Experimental evaluation demonstrated that the application of optimized index structures and parallel processing capabilities can reduce query execution time by an average of 30–40% and ensure more efficient utilization of system resources. At the same time, the proposed architecture maintains stability under high-load conditions and facilitates the formation of a scalable information system. This approach is of practical and applied significance for optimizing the digital management processes of disinfection services.